Applications of bupivacaine in the non-surgical treatments of strabismus: a review. (2nd October 2022) - Kiarudi, Mohammad Yaser; Ghavami Shahri, Seyed Hossein; Es'haghi, Acieh; Gharib, Bahare; Ansari-Astaneh, Mohammad-Reza
ABSTRACT: Bupivacaine (BUP) is an anesthetic from the family of aminoacyl anesthetics and has the highest myotoxicity among other groups of anesthetics. Intramuscular injection of BUP first causes acute libriform lysis and subsequently with the regeneration process, stronger myofibrils are formed within 3–4 weeks. Satellite cells, which are actually myogenic stem cells, are preserved in the early stage and during the destruction of muscle fibers. In fact, these cells are responsible for the subsequent regeneration of fibers. BUP is one of the few medicines that is able to increase muscle strength. In animal studies on rabbits, a decrease has been observed in the diameter of the global layer in the first week and an increase in type-I myosin occurs after 60 days, especially in the global muscle layer. There are numerous studies according to BUP injection for the non-surgical management of horizontal strabismus. To intensify the effects of the injection, botulinum toxin injection can also be used simultaneously in the antagonist muscles. In general, although the rate of improvement in strabismus varied among different studies, BUP injection alone corrects about 5–8 prism diopters. Together with botulinum toxin, BUP corrects about 15 prism diopters. The stability of this improvement is up to 10 years after injection. No significant difference has been observed in response rate between patients with esotropia and exotropia. Unlike the large molecule of botulinum toxin, which spreads slowly to its site of action, the BUP molecule is small and must be in direct contact with myofibrils before absorption into the bloodstream to exert its effect. Therefore, the injection volume should be about 3 cc with a concentration of 0.75 g per deciliter. Although BUP is promising non-surgical strabismus management, especially in small angle and residual horizontal strabismus, however, it has its own limitations. The need for direct infusion of a relatively large volume of BUP may be one of its major drawbacks that limits its usage in an office method.